Durabilidade natural de dez madeiras amazônicas em campo de apodrecimento - Tiesen, Catiane Micheli Alcantara (2017)
The objective of this work was to evaluate the natural durability of the wood of ten Amazonian forest species in two environments of deterioration in the city of Sinop, Mato Grosso. For this, the species studied were the Trattinnickia burserifolia Burseraceae (amescla), Mezilaurus itauba Lauraceae (itaúba), Hymenaea courbaril Fabaceae (jatobá), Nectandra cissiflora Lauraceae (canelão), Hymenolobium petreum Fabaceae (angelim pedra), Erisma uncinatum Vochysiaceae (cedro), Bowdichia virgilioides Fabaceae (sucupira), Apuleia leiocarpa Fabaceae (garapeira), Dipteryx odorata Leguminosae (cumaru) e Qualea albiflora Vochysiaceae (cambara). The environments evaluated were an open field free of undergrowth and a closed forest. The wood samples were made with dimensions of 5 x 5 x 40 cm (width x height x length), and were submitted for approximately two years in a deterioration test in the cited environments and evaluated before and after exposure. In the field, the test of breaking and collecting the termites present in the woods was carried out for later identification. After exposure in the rotting field the wood samples were sent to the laboratory where the sanity index, loss of mass and loss of resistance to parallel compression were determined. The wood of amescla presented less natural durability for all the tests carried out while the woods of itaúba, canelão, garapeira, cumaru and cambara presented greater natural durability. The deterioration environment that most influenced the loss of resistance of the species was the closed forest. Four genera of termites were identified in the evaluated woods, being it Heterotermes sp., Coptotermes sp., Dolichorhinotermes sp. and Armitermes sp. Where the woods most attacked by termites were amescla, angelim stone, cambara and cedro. It is concluded that the environment interferes with the natural durability of wood and the attack of termites.